1994
DOI: 10.1177/014662169401800406
|View full text |Cite
|
Sign up to set email alerts
|

Explanations for Accuracy of the General Multivariate Formulas in Correcting for Range Restriction

Abstract: Univariate and multivariate corrections for range restriction were compared using Navy applicant scores on the Armed Services Vocational Aptitude Battery (ASVAB). Two Navy school ASVAB selector composites were used separately and together to simulate three selection situations for nine selection ratios (SRs). The selectors then were used as predictors. Composite validities (the ASVAB Mechanical Comprehension test was the criterion) were corrected using the univariate and the general multivariate formulas. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Note that γ 1 < 0 in Equation 24 is consistent with prior research (Held & Foley, 1994;Kobrin et al, 2011;Lee & Foley, 1986). It is important to note several properties of the normal distribution.…”
Section: Upper-bound For Monotone Quadratic Functionssupporting
confidence: 72%
See 1 more Smart Citation
“…Note that γ 1 < 0 in Equation 24 is consistent with prior research (Held & Foley, 1994;Kobrin et al, 2011;Lee & Foley, 1986). It is important to note several properties of the normal distribution.…”
Section: Upper-bound For Monotone Quadratic Functionssupporting
confidence: 72%
“…Furthermore, unlike the correction in Equation 1, Assumption 2 allows the prediction errors to be a function of test scores, h (X ). When nonconstant error variance has been detected, prior empirical personnel psychology and educational testing research consistently identified patterns of heteroscedasticity that declines with X (Held & Foley, 1994;Kobrin et al, 2011;Lee & Foley,1986). That is, prediction errors are smaller for higher test scores.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the statistics and economics literature considers the classical "restrictionof-range" problem (DeMets and Halperin, 1977;Duan and Dunlap, 1997;Johnson and Ree, 1994;Held and Foley, 1994;Mendoza et al 1991;Hanges et al 1991;Holmes, 1990). In this literature, correlations, or more generally regression coefficients are shown to be affected by focusing the analysis on a small slice of the population.…”
Section: Relationship To Other Literaturementioning
confidence: 99%
“…This issue of the accuracy of the correction for the range restriction formula under different conditions has been extensively addressed in the literature (e.g., Brewer & Hills, 1969;Greener & Osburn, 1979Gross & Fleischman, 1983;Held & Foley, 1994;Holmes, 1990). It should be noted that no normality assumption is required for range restriction correction formulas (Lawley, 1944;Sackett & Yang, 2000).…”
Section: Confidence Interval Widthmentioning
confidence: 99%